Genetic mutations linked to Parkinson's disease differentially control nucleolar activity in pre-symptomatic mouse models - Evsyukov, Valentin; Mustafa, Rasem; Parlato, Rosanna (Disease models & mechanisms, 2017)
Genetic mutations underlying neurodegenerative disorders impair ribosomal DNA (rDNA) transcription suggesting that nucleolar dysfunction could be a novel pathomechanism in polyglutamine diseases and in certain forms of amyotrophic lateral sclerosis/frontotemporal dementia. Here, we investigated nucleolar activity in pre-symptomatic digenic models of Parkinson's disease (PD) that model the multifactorial aetiology of this disease. To this end, we analysed a novel mouse model mildly overexpressing mutant human α-synuclein (hA53T-SNCA) in a PTEN-induced kinase 1 (PINK1/PARK6) knockout background and mutant mice lacking both DJ-1 (also known as PARK7) and PINK1. We showed that overexpressed hA53T-SNCA localizes to the nucleolus. Moreover, these mutants show a progressive reduction of rDNA transcription linked to a reduced mouse lifespan. By contrast, rDNA transcription is preserved in DJ-1/PINK1 double knockout (DKO) mice. mRNA levels of the nucleolar transcription initiation factor 1A (TIF-IA, also known as RRN3) decrease in the substantia nigra of individuals with PD. Because loss of TIF-IA, as a tool to mimic nucleolar stress, increases oxidative stress and because DJ-1 and PINK1 mutations result in higher vulnerability to oxidative stress, we further explored the synergism between these PD-associated genes and impaired nucleolar function. By the conditional ablation of TIF-IA, we blocked ribosomal RNA (rRNA) synthesis in adult dopaminergic neurons in a DJ-1/PINK1 DKO background. However, the early phenotype of these triple knockout mice was similar to those mice exclusively lacking TIF-IA. These data sustain a model in which loss of DJ-1 and PINK1 does not impair nucleolar activity in a pre-symptomatic stage. This is the first study to analyse nucleolar function in digenic PD models. We can conclude that, at least in these models, the nucleolus is not as severely disrupted as previously shown in DA neurons from PD patients and neurotoxin-based PD mouse models. The results also show that the early increase in rDNA transcription and nucleolar integrity may represent specific homeostatic responses in these digenic pre-symptomatic PD models.